Alleviation of Postharvest Chilling Injury of Carambola Fruit by γ-aminobutyric Acid: Physiological, Biochemical, and Structural Characterization - Ngaffo Mekontso, Francine; Duan, Wenhui; Cisse, El Hadji Malick; Chen, Tianye; Xu, Xiangbin (Frontiers in Nutrition, 2021)
Chilling injury is a physiological disorder affecting the quality of carambola fruit. In the present study, the effect of exogenous γ-aminobutyric acid (GABA) on CI development in carambola fruit during storage at 4°C for 15 days was investigated. The results showed that 2.5-mM GABA reduced CI index, maintained pericarp lightness, and decreased the electrolyte leakage (EL) and malondialdehyde content (MDA) while increased the superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) enzyme activities. Endogenous GABA content was significantly higher in the treated fruit than in the control fruit during the whole storage. Besides, the treatment promoted the accumulation of proline and ascorbic acid (AsA) under chilling stress. Compared to the control, GABA-treated fruit exhibited a higher activity of phenylalanine ammonia-lyase (PAL) and total phenolic compounds, and a lower activity of polyphenol oxidase (PPO). In addition, the Safranin O/fast green staining revealed via microscopic images that the GABA treatment reduced the cell walls degradation of carambola fruit. Moreover, the results displayed a lower activity of phospholipase D (PLD) and lipoxygenase (LOX) enzymes, which coincided with a higher content of oleic acid (C18:1), linoleic acid (C18:2n6), and α-linolenic acid (C18:3n3) after 15 days of treatment, leading to the maintenance of the integrity and prevention of the membrane of the rapid softening of carambola fruit. The findings of the present work showed particularly new insights into the crosstalk between GABA and fatty acids. GABA might preserve the pericarp of carambola fruit by increasing the content of the unsaturated fatty acid (UFA) γ-linolenic acid and reducing the saturated fatty acid (SFA) such as caproic acid (C6:0), caprylic acid (C8:0), myristic acid (C14:0), and palmitic acid (C16:0) progressively. GABA can be used as an appropriate postharvest technology for improving the quality of carambola fruit during low-temperature storage.